LITURGI ADAPTIF SEBAGAI MEDIUM KONEKTIVITAS ANTARGENERASI DALAM IBADAH KRISTEN : KAJIAN TEOLOGIS DAN PRAKTIS DALAM KONTEKS DI "SYALOM” LELEMA - Eunike Karunia Natasya Sumual (MATA GURU: Jurnal Pendidik dan Tenaga Kependidikan, 2025)
This study explores the role of adaptive liturgy as a medium for intergenerational connectivity in Christian worship. Generational diversity within congregations often creates gaps in worship experiences, necessitating a liturgical approach capable of embracing all ages. Utilizing a theological and practical study with a qualitative case study approach through observation and literature review at GMIM "Syalom" Lelema, this research finds that adaptive liturgy effectively facilitates intergenerational connectivity. Key findings indicate the practice of reciprocal participation in major church celebrations and worship processions involving all generations, as well as the adaptation of worship music where old songs are rearranged in a contemporary style to attract younger generations without alienating older ones. The analysis of these findings within the theoretical framework strengthens their significance. The liturgical practices at GMIM "Syalom" Lelema align with Communication Accommodation Theory (CAT) in adjusting communication styles, Social and Cultural Adaptation Theory in responding to congregational dynamics, Participatory Ecclesiology Theology which encourages collective involvement, and the Principle of Unity in Diversity, which unifies differences in harmony. It is concluded that adaptive liturgy at GMIM "Syalom" Lelema is a concrete model that successfully bridges generational gaps, forming an inclusive, participatory, and unified church in diversity. This research contributes to the literature on practical theology and liturgy by providing an empirical case study from the Indonesian context, offering practical guidance for other churches.